Integrated safety and economic factors in a sand mine industry: a multivariate algorithm. (22nd July 2019) - Babajani, Reza; Abbasi, Mohammad; Azar, Ahmad Taher; Bastan, Mahdi; Yazdanparast, Reza; Hamid, Mahdi
Performance evaluation and optimisation of safety factors is a crucial need for almost all industries. This need is highlighted in some critical industries such as the mining industry. Health and economic loss in mining accidents are significant, especially in developing countries which lack modern technologies. This paper applies resilience engineering as a relatively new approach toward safety analysis in a sand mine in Iran. To this end, a comprehensive framework is proposed based on the Resilience Engineering (RE), Fuzzy Data Envelopment Analysis (FDEA) and statistical methods. FDEA is applied to measure efficiency scores of resilience engineering factors. Sensitivity analysis of obtained efficiency scores is employed by statistical methods. The obtained results are validated and verified. The results indicate Injury Severity Score (ISS), number of injuries and Accident Frequently Rate (AFR) as the most effective factors on safety performance.